DOES TALENT MANAGEMENT AFFECT ORGANIZATION PERFORMANCE IN ELECTRONICS MANUFACTURING BATAM? - Manurung, Windy Octaviana; Fatyandri, Adi Neka (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2024)
The research focuses on the influence of talent management on organizational performance, mediated organizational commitment and moderation of transformational leadership. This study is a quantitative study that distributes questionnaires to employees of electronics manufacturing companies in Batam City of 352 respondents, analyzed using the SmartPLS method. The results of the research show that talent management has a significant influence on organizational performance through direct influence tests and its influence becomes insignificant and not mediated by organizational commitment. Organizational commitments, consisting of the dimensions of affective commitment, continuance commitment and normative commitment also have a significant impact on organizational performance, suggesting that employees who are committed to the organization tend to make a better contribution to the company's performance. Transformational leadership has a significant influence on organizational performance directly, when tested as a moderation variable its influence becomes insignificant. This research gives some recommendations; the importance of employee development through training and talent development to improve company performance.